Clinical Presentation and Outcome of COVID-19 Infected Cancer Patients: A Prospective Study - Rahman, Shaila; Bahar, Tamanna; Wazib, Amit; Chowdhury, Zulfia Zinat; Hossain, Mohammad Murad; Anne, Rifat Taher; Begum, Shamim Ara (Bangladesh Journal of Medicine, 2021)
Background: Patients with active cancer are considered to be a high-risk group during the COVID- 19 pandemic. Reports of studies on the impact of COVID-19 infection on cancer patients in Bangladesh are sparse. This study was conducted to describe the clinical presentation and assess the outcome of COVID-19 infected cancer patients. Methods: In this prospective study, we enrolled 43 patients with active cancer from different cancer hospitals in Dhaka, Bangladesh who were tested positive for RTPCR of COVID-19. The study period was from August to October 2020 (three months) following ethical approval and informed written consent was ensured. The data were collected in a structured questionnaire form by interviewing the patients/relatives and from medical records of inpatient and outpatient departments and analyzed by SPSS version 25. Results: The mean age of the 43 study participants was 49.2 (±13.6) years with a male predominance (60.5%). The common primary malignancies were leukaemia (27.9%), carcinoma of the colon (18.6%), and carcinoma of the breast (14%). Diabetes (30.2%) and hypertension (27.9%) were the common co-morbidities. The most frequently found symptoms were fever and cough 67.4% each. Severe and critical illness were found in 27.9% and 2.3% cases respectively. 35 (81%) patients survived from COVID-19 and death was observed in 8 (19%) patients.There was no significant association of age, gender, primary malignancy type, and major co-morbidities with the outcome. Severe and critical illness were found to be significantly associated with higher mortality. Conclusions: COVID-19 related mortality is higher in cancer patients than in the general population. Mortality depends on the severity of COVID-19 in these patients, associated with severe & critical cases. Bangladesh J Medicine July 2021; 32(2) : 90-94